362 ROLE OF ACETYLCHOLINE IN PSYCHOSTIMULANT ADDICTION. (1st January 2006) - Kumar, T.; Joyce, J. A.; Bamford, N. S.
Abstract : Background: The basal ganglia play an important role in drug dependence. Excitatory glutamatergic projections from the cerebral cortex innervate the basal ganglia at the striatal medium spiny neuron, which also receives modulatory dopaminergic and cholinergic projections. This anatomical relationship suggests that chronic elevation of dopamine by METH may disrupt the release of both glutamate and acetylcholine (ACh). Investigations in our laboratory have demonstrated that treatment of mice with chronic METH results in a long-lasting depression of glutamate release from cortical terminals during withdrawal that is dependent on ACh. In this study, we determined how chronic METH treatment in mice changes the synthesis and activation of striatal cholinergic interneurons. Study Design and Methods: Adult C57B1/6 mice were treated with METH (20 mg/kg i.p.) or saline for 10 days. On withdrawal days 1 and 10, brain sections were immunolabeled for choline acetyltransferase (ChAT) and c-Fos. Labeled cells from three rostrocaudal levels were quantified in the dorsomedial and dorsolateral striatum and in the nucleus accumbens (NAc). Results: On withdrawal day 1, sections from METH-treated mice demonstrated only rare and poorly fluorescent ChAT immunolabeled cells. Compared to controls, c-Fos immunoreactivity was largely absent from the striatum, suggesting that chronic METH results in the depression of immediate early gene expression in both cholinergic and medium spiny neurons. On withdrawal day 10, the number of ChAT-immunostained cells in the striatum had increased but remained depressed compared with controls. Persistent depression was most prominent in the caudal striatum where ChAT-immunolabeled cells were reduced by 16.8% ± 1.6% compared to controls ( p = .014). The number of immunolabeled cells for both ACh and c-Fos were also reduced in all striatal regions. This reduction was more pronounced in the caudal NAc ( p = .08) and dorsolateral striatum ( p = .09), but high variability between mice prevented reaching statistical significance. Conclusion: Our data suggest that chronic METH reduces both ACh synthesis and cholinergic activation. This reduction is likely mediated by persistent stimulation of dopamine receptors on cholinergic interneurons, ultimately leading to a reduction in striatal excitation. Future experiments will examine the effect of a drug challenge on ACh production and cholinergic activation.